Phytochemical and Biological Studies on Zanthoxylum Armatum of Nepal - Joshi, Sushika; Gyawali, Anuradha (Journal of Nepal Chemical Society, 2013)
Phytochemical and biological screening of stem extracts of Zanthoxylum armatum of Nepal were carried out. Presence of sterols, triterpenes, volatile oils, coumarins, alkaloids, flavonoids, flavonic glycosides, saponins and tannins were detected in phytochemical screening. β-sitosterol and lupeol were isolated from the hexane fraction and β-sitosterol glucoside was isolated from the ethyl acetate fraction. Lupeol was identified by comparison of melting point, Co-TLC and 1H-NMR spectrum with authentic sample. β-sitosterol and β-sitosterol glucoside were characterized by their melting points and Co-TLC with authentic samples. In brine-shrimp bioassay, hexane and methanol fractions exhibited bioactivity, whereas ethyl acetate and methanol fractions showed proper bioactivity in antimicrobial bioassay.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9339Journal of Nepal Chemical Society Vol. 30, 2012 Page:  71-77 Uploaded date: 12/16/2013